Positive and Negative Team Identity in a Promotion Game - Marion Eberlein; Gari Walkowitz (University of Bonn, Bonn Graduate School of Economics (BGSE), 2008)
In this paper we experimentally investigate whether the so-called in-group/out-group bias leads to a favoring of own team members as candidates in promotion (by voting for them) relative to other teams and their members. In contrast to psychological approaches, mon- etary incentives for voting choices are implemented and objective performance criteria defined and thus the extent of the in-group/out-group bias is exactly measured. Our data show that face-to-face interaction with team members leads more subjects to favor own team-mates than in anonymous interaction. Moreover, not only the frequency but also the average extent of positive team identity is higher with face-to-face interaction according to objective performance measures. A further finding suggests that only anonymous team interaction often leads to substantial discrimination of own team members (i.e., negative team identity), which also is an interesting new finding and extends previous indings of psychologists on the in-group/out-group bias.
Keywords: M5; L2; C9; 330; Team identity; promotion; experiments; Erwerbsverlauf; Gruppenarbeit; Soziale Beziehungen; Wahlverhalten; Test